Intragraft Donor‐Specific Antibody Detection: A New Test to Dichotomize HLA Alloantibodies Into High and Low Injurious Activity. Issue 11 (18th September 2013) - Sis, B.
Abstract : Intragraft antibody detection opens new avenues for research and clinical decision‐making. See article by Bachelet et al on page 2855.